The relationship between task – technology fit and job perfomance a study among meter reader at Syarikat Air Melaka Berhad (SAMB) / Adilah Alias - Alias, Adilah (Faculty of Business and Management, 2013)
This study identified the relationship between task-technology fit and job performance among meter reader at Syarikat Air Melaka Berhad. The research questions conducted defined the significant relationship between task-technology fit and job performance which divided into eight measurements that falls under task..:technology fit. This study was conducted among meter readers at Syarikat Air Melaka Berhad with the total respondents of 66 whom are among different grades of position. There are no sampling techniques in deciding sample since this study involved every meter reader at Syarikat Air Melaka Berhad. Pearson correlation analysis conducted between each tasktechnology fit's factors. The eight measurement involved was quality, locatability, authorization, compatibility, production timeliness, systems reliability, ease of use or training and relationship with users. A weak ~orrelation appears in between independent and dependent variable job perforlnance which are locatability, authorization, cOlnpatibility and systems reliability. Meanwhile, a moderate relationship occurs between quality, production timeliness, ease of use or .training and relationship with users. Other than that, this study also suggest for larger sample size in the future for further fully identifying the significant relationship between these both variables in other condition and situation.